NF-κB c-Rel is a critical regulator of TLR7-induced inflammation in psoriasisResearch in context - Angela Rose Liu; Nandini Sarkar; Jordan D. Cress; Tristan J. de Jesus; Ananya Vadlakonda; Joshua T. Centore; Alexis D. Griffith; Bethany Rohr; Thomas S. McCormick; Kevin D. Cooper; Parameswaran Ramakrishnan (EBioMedicine)
Summary: Background: Nuclear factor kappa B (NF-κB) c-Rel is a psoriasis susceptibility locus, however mechanisms underlying c-Rel transactivation during disease are poorly understood. Inflammation in psoriasis can be triggered following Toll-like Receptor 7 (TLR7) signalling in dendritic cells (DCs), and c-Rel is a critical regulator of DC function. Here, we studied the mechanism of TLR7-induced c-Rel-mediated inflammation in DCs. Methods: The overall expression of c-Rel was analysed in skin sections from patients with psoriasis in human transcriptomics datasets as well as the imiquimod-induced psoriasis mouse model. The function of c-Rel in DCs following TLR7 stimulation was determined by c-Rel CRISPR/Cas9 knockout DC2.4 immortalised cells and primary bone marrow derived dendritic cells from c-Rel knockout C57BL6/J mice. Findings: c-Rel is highly expressed in lesional skin of patients with psoriasis and TLR7-induced psoriatic lesions in mice. c-Rel deficiency protected mice from the disease, and specifically compromised TLR7-induced, and not TLR9- or TLR3-induced, inflammation in dendritic cells. Mechanistically, c-Rel deficiency disrupted activating NF-κB dimers and allowed binding of inhibitory NF-κB homodimers to the IL-1β and IL-6 promoters thus inhibiting their expression. This functionally compromises the ability of c-Rel deficient DCs to induce Th17 polarisation, which is critical in psoriasis pathogenesis. Interpretation: Our findings reveal that c-Rel is a key regulator of TLR7-mediated dendritic cell-dependent inflammation, and that targeting c-Rel-dependent signalling could prove an effective strategy to dampen excessive inflammation in TLR7-related skin inflammation. Funding: A complete list of funding sources that contributed to this study can be found in the Acknowledgements section.